Let $G$ be a group and let $\phi:G \rightarrow G$ be defined by $\phi(g)=g^{-1}$. Prove that $\phi$ is an isomorphism if and only if $G$ is abelian.

My attempt.

(Forward direction)

Suppose $\phi$ is isomorphic. Then $\phi$ is:

$i)$ Injective. Implying that $\phi(g_1)=\phi(g_2), g_1=g_2$

$ii)$ Surjective. Implying that $a^{-1} \in G$ and $\phi(a)=a^{-1}$

$iii)$ $\phi(g_1g_2)$ = $\phi(g_1)\phi(g_2)$

from ($iii)$, $\phi(g_1g_2) =\phi(g_1)\phi(g_2)= g_1^{-1} g_2^{-1}$

=$\phi(g_2)\phi(g_1^{-1})\phi(g_1)\phi(g_2)\phi(g_2^{-1})\phi(g_1)= g_2^{-1}g_1g_1^{-1} g_2^{-1}g_2g_1^{-1}= g_2^{-1}g1^{-1} = \phi(g_2)\phi(g_1)$

Hence, it is abelian.

(backwards direction)

Suppose $\phi$ is abelian. Then $\phi(g_1 g_2) = g_2^{-1} g_1{^-1}$

To show injectivity: Let $\phi(g_1g_2) = \phi(g_2g_1)$

$g_1^{-1}g_2^{-1}= g_2^{-1}g_1^{-1}$


$e_1 = e_2$

Surjectivity follows by definition.

Finally, from similar to the forward direction, $\phi(g_1g_2)=\phi(g_1)\phi(g_2)$

  • 2
    $\begingroup$ I do not think that the first direction is coherent. You should start with let $g_1,g_2 \in G$ and show that $g_1g_2=g_2g_1$, which you haven't done. Also, the "injective" statement doesn't make sense. It should be $\phi(g_1)=\phi(g_2) \implies g_1=g_2$. This is not the only way to do the proof, but as written, I can't follow the logic. $\endgroup$ – Andres Mejia Nov 2 '16 at 21:18

Assume $G$ is abelian and let $a,b \in G$. $\phi(ab) = (ab)^{-1} = b^{-1}a^{-1} = a^{-1}b^{-1} = \phi(a)\phi(b)$. $\phi$ is obviously surjective by construction. Suppose that $\phi(a) = \phi(b)$, then $a^{-1} = b^{-1} \longrightarrow aa^{-1}b = ab^{-1}b \longrightarrow b = a$. Thus $\phi$ is injective.

Now suppose that $\phi$ is an isomorphism. Then $\phi(ab) = \phi(a)\phi(b) = a^{-1}b^{-1}$ implies that $(ab)^{-1} = b^{-1}a^{-1} = a^{-1}b^{-1}$. Thus $G$ is abelian.


$\phi$ itself is one-to-one and onto without the condition that $G$ is abelian.

Suppose $\phi(g_1)=\phi(g_2)$ where $g_1,g_2\in G$
We have $g_1^{-1}=g_2^{-1}$
Since the inverse of an element is unique in a group,
$g_1=g_2$ which implies $\phi$ is one-to-one.

Let $y\in G$
Then $y^{-1}\in G$ where $\phi(y^{-1})=(y^{-1})^{-1}=y$
Thus $\phi$ is onto.

So the question now become Prove that $\phi$ is a homomorphism iff $G$ is abelian.

Suppose $\phi$ is a homomorphism.
Let $g_1,g_2\in G$
Then $\phi(g_1g_2)=\phi(g_1)\phi(g_2)$
So $(g_1g_2)^{-1}=g_1^{-1}g_2^{-1}=(g_2g_1)^{-1}$
Again since the inverse of an element is unique,
$g_1g_2=g_2g_1$, we conclude $G$ is abelian.

Suppose $G$ is abelian. Let $g_1,g_2\in G$
Then $\phi(g_1g_2)=(g_1g_2)^{-1}=g_2^{-1}g_1^{-1}=g_1^{-1}g_2^{-1}=\phi(g_1)\phi(g_2)$ We conclude that $\phi$ is a homomorphism.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.